THE INFLUENCE OF THE MORAL REASONING METHOD ON STUDENTS’ ANALYTICAL THINKING THROUGH SELF-EFFICACY IN THE AKIDAH AKHLAK SUBJECT AT MAN 2 BONE REGENCY - Andi Suci Wahyuni; Amir B; Arisal Arsyad; Aksi Hamzah (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the direct influence of the methodMoral Reasoningtowards abilityanalytical thinkingand self-efficacy of students in learning Akidah Akhlak, and examine the role of self-efficacy as a mediator in this relationship. The background of this research is based on the urgency of implementing learning methods that not only optimize cognitive aspects but also strengthen students' self-confidence in facing academic challenges, especially in the context of Islamic religious education. This study uses a quantitative approach with an explanatory design, involving a sample of class XI students of MAN 2 Bone Regency who were selected proportionally. Data were collected through a questionnaire that has passed the validity and reliability tests, then analyzed usingPartial Least Square Structural Equation Modeling(PLS-SEM). The results of the study show that the methodMoral Reasoning directly improves students' analytical thinking skills and self-efficacy. In addition, self-efficacy has been shown to play an important role as a mediator that strengthens the influence of learning methods.Moral Reasoningon analytical thinking skills. This finding confirms that the effectiveness of the methodMoral ReasoningIn learning, does not only depend on the teaching strategies used, but also on strengthening students' self-confidence.